The fallacy of participation in behaviour change programming: the case of Gweru Women AIDS Prevention Association (GWAPA), Zimbabwe - Mushuku, Patience Priscilla (David Publishing, 2016)
Gweru Women AIDS Prevention Association (GWAPA) is an organization that works with commercial sex-workers in the Midlands Province to try and stymie the tide of HIV/AIDS. The organization premises its activities upon the belief that sex workers are forced into prostitution by poverty and thus offers them alternative livelihood strategies such as piggery projects, chicken rearing, and vegetable vending projects as well as seed money with which to start flea market projects. The organization also runs a condom promotion project, a legal literacy project, and an advocacy project, all in a bid to empower the sex workers cognitively. The study was carried out between April and October 2008, using bar-based observations, interviews, focus group discussions, and documentary evidence. The study found participation to have been more of a fallacy in as far as programming depended more on the whims of donor funders than the actual needs of programme beneficiaries. In the top-down manner that is typical of development communication, the organization would engage donors and secure funding for certain projects which they would then try to convince the sex workers to take up, with mixed results. The research also found limited evidence of real empowerment of beneficiaries in the long run, with the sex workers themselves insisting that the ―piece-meal‖ efforts of the organization were not sustainable enough to induce them to abandon sex work altogether. The study did, however, find that the organization and its programming had actually managed to score notable success in promoting safer sex within the context of prostitution, albeit without eradicating sex work altogether.